ESTIMATED INCIDENCE OF TUBERCULOSIS IN NEW MIGRANT WORKERS WITH CONSIDERATION OF THEIR AGE AND GENDER - A. V. Ershovа; S. A. Sterlikov (Туберкулез и болезни лёгких, 2018)
The objective of the study: to estimate the age and gender-related and standardized incidence of tuberculosis in migrants versus incidence of tuberculosis in the countries of their origin and resident population.Subjects and Methods. Age and gender-related and standardized incidences of tuberculosis in the migrants were compared as well as incidence in the countries of their origin and among the resident population in Kaliningrad Region.Results. The standardized incidence of tuberculosis in the migrants is compatible with the incidence in the countries of their origin but it is two-fold higher versus the incidence among resident population. Tuberculosis incidence is higher in migrants compared to the population in the countries of their origin and residents of Kaliningrad Region in the age of 7-14 and 18-24 years old which is related to screening deficiencies in the countries of origin. No gender-related specific features of tuberculosis incidence were found in migrants.Conclusions. The standardized incidence in migrants corresponds to the standardized incidence in the countries of their origin, however, it is twice higher compared to the resident population of Kaliningrad Region. It would be appropriate to consider screening for tuberculosis in migrants in the age of 7-14 and 18-24 years old. Data on age and gender of migrants allow accurate estimation of their contribution to incidence of tuberculosis.